2017
DOI: 10.1016/j.socscimed.2016.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Relation between social network and psychological distress among middle-aged adults in Japan: Evidence from a national longitudinal survey

Abstract: It is widely documented that psychological distress is negatively associated with social networks involvement. However, despite the theoretical postulations that social networks are crucial for alleviating psychological distress, no study has yet empirically confirmed the causality of this relationship. Thus, we used the random-effects generalized least squares method to investigate the effect of one- and two-year lagged values for involvement in social networks on psychological distress. Nine years of longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
8
15
0
Order By: Relevance
“…Both the descriptive and regression analyses showed that the engagement in SP had a positive impact on health outcomes in later waves. These results were generally in line with those in previous studies that dealt with related issues in China [21][22][23] as well as outside the country [1][2][3][4][5][6][7][8][9][10][11][12][13][14]27].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Both the descriptive and regression analyses showed that the engagement in SP had a positive impact on health outcomes in later waves. These results were generally in line with those in previous studies that dealt with related issues in China [21][22][23] as well as outside the country [1][2][3][4][5][6][7][8][9][10][11][12][13][14]27].…”
Section: Discussionsupporting
confidence: 92%
“…Among others, four findings are noteworthy. First, the positive impact of SP was remarkable for mental health as well as ADL, a result consistent with the findings in the previous studies in the developed countries [6][7][8][9][10][11]. The number of patients with mental health disorder has been increasing in China in recent years.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Several studies have demonstrated that SP experiences prevent the onset of diseases and functional disability [1][2][3][4][5], mental health disorder [7][8][9][10][11][12], cognitive impairment [3,8,13], and delayed mortality [14,15] among the elderly. Interactions with others in society or a community-considered core aspects of SP and closely related to the concept of hedonic stock-are expected to accelerate adaptation to health shocks, as well as prevent their onsets [16].…”
Section: Introductionmentioning
confidence: 99%